Security Issues with Contactless Bank Cards - McBride, Brendan; McKelvey, Nigel; Curran, Kevin (Journal of Information, 2015)
Contactless bank cards have been issued steadily to banking customers over the past four years and this trend has continued to grow rapidly more recently. We want to highlight a list of security issues as well as privacy threats to be concerned with when using such contactless bank cards. Further advances in smartphone technology applications can lead to new threats in relation to contactless bank cards. This study contributes to the literature as it highlights data protection issues in Ireland and also highlights the major push by authorities to adopt a cashless banking society which could potentially lead to further data protection problems in Ireland.